Evaluasi Penggunaan Flexible Pavement dan Rigid Pavement di Atas Tanah Berdaya Dukung Rendah Dilihat Dari Aspek Biaya(Studi kasus Jalan Ngerangan -Kalisogo dan Cawas - Pakisan) - SHODIQ , MUHAMMAD ANWAR (2011)
The District of Klaten lies between two neighboring cities, namely Yogyakarta and Surakarta, resulting in increased transport demand and eventually leading to traffic density. The connecting streets from Cawas to Pakisan and from Ngerangan to Kalisogo are roads with unstable soil conditions to support them. Those roads are also in a project site of Digging Area C and an alternative way to some towns in the District of Gunung Kidul and Sukoharjo. The District of Klaten built those roads using Flexible and Rigid pavement construction. The question here is how much had the budget been spent for the construction and maintenance for the past twenty years? This was a study to calculate the costs of construction and maintenance of both roads for 20 twenty years. The method was used to determine the location of Cawas - Pakisan road for the rigid pavement construction and Ngerangan - Kalisogo road for flexible pavement construction and sources of secondary data obtained from related institutions, in calculating costs for Rigid pavement construction in 20 years and for Flexible pavement construction in 5 years . The result showed that the cost of construction including construction of flexible pavement maintenance costs in supporting low-power ground conditions, length of road 450 m and wide 5 m with a level of service B and peak hour volume of 1902 vehicles, Jl.Ngerangan- kalisogo is more suitable to be applied if the condition of interest bank interest 12% and 18%, with inflation rate 6% while segment jl.Cawas-Pakisan is more suitable to be applied if the conditions of bank interest rate of 6% with inflation rate 6%.